Morphological Evaluation of the Subaxial Cervical Spine in Patients with Basilar Invagination: A CT-based Study. Issue 20 (15th October 2021) - Lin, Shaoyi; Bao, Minggui; Wang, Zihan; Zou, Xiaobao; Ge, Su; Ma, Xiangyang; Chen, Jianting; Ji, Wei; Yang, Jincheng
Abstract : Study Design: Retrospective study. Objective: To evaluate the morphologic features of the subaixal cervical spine in patients with basilar invagination (BI) and provide information for the accurate screw placement in this region. Summary of Background Data: BI is a congenital anomaly, comprising a wide range of abnormal structures. The screw fixation can be required in situation that BI is combined with subaxial cervical spine pathologies. However, there are no literatures specifically addressed the subaxial cervical morphology of BI. Method: A total of 42 BI patients were included in this retrospective study. Forty-two patients without head or cervical disease were matched for sexes and ages. Information on radiographic features of the subaxial cervical spine was collected and compared systematically. Results: There were no differences in the age and sex between the BI and control group. The BI group manifested a wider pedicle and laminar than the control group at all cervical levels, except for the pedicle of C6 and C7, and the laminar of C3 and C6. In addition, the BI group had a wider lateral mass from C3 to C5 than the control group. There were no differences in most measurements of the length of pedicle, laminar, and lateral mass. Conclusion: BI patients have a wider pedicle and laminar than the general population in the subaxial cervical spine, but the same size in length of pedicle, laminar, and lateral mass. Level of Evidence: 4 Abstract : Basilar invagination is a common deformity in the cervical spine. The screw fixation can be required in situation that basilar invagination is combined with other subaxial cervical spine pathologies. In this study, we assessed the C3–C7 morphologic features of BI patients to instruct the accurate screw placement in this region.